Strategic Management and Waqf : A Proposition - Tiara Puspa (Universitas Trisakti, 2018)
These studies build proposition about waqf as become one competitive advantage issue which develops under a model of management strategy. Although there was three step in that model, these study only discuss the first step which is formulation strategy to determine external factors that considerate opportunity and threats. A lot of threats comes from the situation like the habit to give priority into physical needs, ages such as biographical characteristics, investor mindset, government policy, and globalization could be factors that hinder people from doing waqf. Beside that nazir attitude and behavior explained strength and weakness managing waqf. Although these study only describes the proposition, as a basic idea to do next research, but its gives a contribution on how to proof factors that shape threats and opportunity to formulate a strategy implement waqf successfully. Key Words : Strategy, Waqf, Opportunity, Threats, Strength, Opportunity